2019
DOI: 10.21009/spektra.041.02
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Poly (Ethylene Glycol) on the Photoluminescence Properties of Carbon Dots From Cassava Peels Synthesized by Hydrothermal Methods

Abstract: Carbon dots (C-dots) have been successfully synthesized from cassava peels using the hydrothermal method. The C-dots are further passivated using poly (ethylene glycol) (PEG) with a variation of the volume of 0.5 ml, 1.0 ml, and 1.5 ml. The properties of photoluminescence C-dots before and after PEG were characterized using photoluminescence (PL) and time-resolved photoluminescence (TRPL) spectrophotometers. PEG succeeded in influencing PL C-dots properties, such as peak wavelength, PL intensity, and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The photoluminescence process can be observed in the position of the spectrum, dynamics, and efficiency to obtain relevant information. This spectrum informs about the energy difference between the excited state and the ground state which serves as the first indicator of material application [7,25].…”
Section: The Photoluminescence Spectroscopy Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The photoluminescence process can be observed in the position of the spectrum, dynamics, and efficiency to obtain relevant information. This spectrum informs about the energy difference between the excited state and the ground state which serves as the first indicator of material application [7,25].…”
Section: The Photoluminescence Spectroscopy Analysismentioning
confidence: 99%
“…Putro et al reported that outer cassava peels can be synthesized easily using microwave-assisted [6]. Therefore, inner cassava peels also can be synthesized by hydrothermal methods [7], microwave [8], and simple carbonization in an oven [4]. Some of the featuring properties of C-dots are independent excitation-photoluminescence [9] and electrical conductivity [10], which are potential applications as optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing a 1064 nm Nd:YAG laser, we pursue the synthesis of CDs, delving into their optical characteristics, morphology, and size (Kaczmarek et al, 2021;Reyes et al, 2016). We meticulously quantify the energy absorption of CDs pre and post laser ablation, and upon integration with PEG400, adopting ImageJ for fluorescence intensity analysis in zebrafish ocular regions (Aji et al, 2017;Putro et al, 2019;Gao et al, 2020). Employing the Corrected Total Cell Fluorescence (CTCF) technique, we assess the fluorescence density across multiple image slices acquired via CLSM (Jakic et al, 2017), thereby enhancing our understanding of CDs' potential in bioimaging.…”
Section: Introductionmentioning
confidence: 99%